Applicability of phytoplankton diversity and trophic state indices as indicators of the eutrophication process in the areas of the Rio Grande branch and Central Body of the Billings reservoir (Research, Society and Development, 2024)
The phytoplankton structure is influenced by environmental factors, seasonal cycles and trophic degree of the system. The objective of the present study was to identify how the diversity of phytoplankton species responds to environmental factors such as the seasonality and the trophic state of the Billings reservoir, located in the Metropolitan Region of São Paulo (RMSP). Physicochemical and biological variables were analyzed in Central Body (CC) and Rio Grande branch (RG), throughout a seasonal cycle (February to November 2020; n = 6). Phytoplankton density was obtained by counting organisms per mL and the diversity, richness and evenness indices were calculated. The calculation of the trophic state index showed a gradient in the trophic degree, with RG being characterized as mesotrophic and CC as eutrophic. The phytoplankton composition consisted of 138 taxa, 34 of which were recorded exclusively in CC and 33 recorded only in RG. Taxonomic richness, diversity and equitability showed small variation in CC and RG. Phytoplankton abundance varied spatially and temporally. The highest densities were recorded in CC, with the cyanobacteria group being the most representative (contribution of 80%). In RG, in addition to cyanobacteria, a contribution from green algae and diatoms was recorded. Phytoplankton proved to be a sensitive tool for monitoring the dynamics of eutrophication processes and the formation of algal and cyanobacterial blooms.